Discharge rate consistency of each channel for UAV-based pneumatic granular fertilizer spreader - Wang, Xunwei; Jiang, Rui; Zhou, Zhiyan; Song, Cancan; Luo, Xiwen; Bao, Ruifeng; Lyu, Zichen; Huang, Junhao; Lin, Jianqin (International Journal of Agricultural and Biological Engineering, 2023)
Unmanned aerial vehicles (UAVs) are widely being used to spread granular fertilizer in China. Granular fertilizer spreaders equipped with UAVs are mainly centrifugal disc-type and pneumatic. The multichannel pneumatic granular fertilizer spreaders (MPGFSs) have a banded fertilizer deposition distribution pattern, which are more suitable for variable rate fertilization than the circular deposition distribution pattern of disc-type granular fertilizer spreaders (DGFSs). However, the existing MPGFS has the disadvantage of inconsistent discharge rate of each channel, which affects the uniformity of fertilization. In order to explore the causes of inconsistent discharge rate of each channel, the discrete element method (DEM) and bench test were performed to analysis the discharge process of the fluted roller fertilizing apparatus and distribution of fertilizer in axial direction of fluted roller. The computational fluid dynamics (CFD) was used to simulate the airflow field of pneumatic system to analyze the influence of airflow on the movement of fertilizer particles. The simulation results of the discharge process of the fluted roller fertilizing apparatus showed that the filling velocity at the axial ends of the fluted roller fertilizing apparatus was lower than that of the middle. The reason was that the filling capacity was weak near the wall. The simulated results of the airflow field without partitions showed that the airflow provided by the axial flow fan was rotational, and this caused the particles to move irregularly in the throat, resulting in inconsistency discharge rate of each channel. Based on the analysis of reasons of inconsistent discharge rate of each channel, a MPGFS with partitions in the throat was developed. The discharge rate bench tests were carried out to optimize the partition spacing parameters, and fertilization test was performed to test the performance of the improved MPGFS. The discharge rate test results showed better consistency with partition. The coefficient of variation (CV) of the discharge rate of each channel was 20.16% without the partition and 7.70% with the optimal partition. The fertilizer spreading uniformity test results shown that the CV of spreading uniformity of MPGFS without partitions was 15.32%, and that MPGFS with partitions was 8.69%. The partitions design was beneficial to improve the consistency of each channel discharge rate and the uniformity of fertilization. The finding can provide a strong reference to design the MPGFS. Keywords: UAV, discharge rate, fertilizer spreader, DEM, CFD DOI: 10.25165/j.ijabe.20231604.7129 Citation: Wang X W, Jiang R, Zhou Z Y, Song C C, Luo X W, Bao R F, et al. Discharge rate consistency of each channel for UAV-based pneumatic granular fertilizer spreader. Int J Agric & Biol Eng, 2023; 16(4): 20-28